Capital Market Masterplan 3: Strengthening Malaysia’s Islamic Capital Market for Sustainable Growth: Rencana Induk Pasar Modal 3: Memperkuat Pasar Modal Islam Malaysia untuk Pertumbuhan Berkelanjutan - Amirul Afif Muhamat; Mohamad Nizam Jaafar; Nor Azidah Mohd Zahari (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2025)
The Capital Market Masterplan 3 (CMP3), introduced by the Securities Commission Malaysia in 2021, provides a strategic five-year framework to advance Malaysia’s Islamic Capital Market (ICM). It aligns Shariah-compliant finance with global sustainability objectives, digital innovation and financial inclusion. This paper examines CMP3’s six strategic pillars catalyzing competitive growth; empowering investors; shaping the stakeholder economy; embedding shared accountability; prioritizing efficiency outcomes; and embracing technology and assesses their grounding in Maqasid al-Shariah and ESG principles. Drawing on qualitative policy analysis and market statistics, this study shows how CMP3 enhances market resilience, broadens access for MSMEs and mid-tier firms, and positions Malaysia as a global Islamic finance hub. This study concludes with recommendations to strengthen regulatory support, harmonize Shariah governance and accelerate digital transformation to realize CMP3’s vision fully.